Exploration of Talent Cultivation and Curriculum Construction for the Five Year Unified System - Zhang, Yingying (Journal of Theory and Practice of Contemporary Education, 2023)
Introduced the design elements of a five-year consistent talent training plan for the electronics major, provided training objectives and professional abilities, constructed a curriculum system for connecting vocational and secondary schools, and demonstrated in detail the requirements for knowledge and skills points in the electrical and electronic technology course. Designed the selection principles and assessment plan for vocational and secondary school students to be promoted to vocational colleges.